Students' passion for learning without cheating behaviour - Lahagu, Mesrawati (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
The purpose of this study was to find out the background of students' enthusiasm for learning in class VIII-1 without cheating behaviour at UPTD SMP Negeri 3 Mandrehe Utara. What makes students active in learning but when doing assignments or exams do not cheat. The focus of the research is the spirit of learning of students without cheating behaviour. The research approach used is qualitative with the observation method. The subjects in this Journal are six students at UPTD SMP Negeri 3 Mandrehe Utara from class VIII-1. The results showed that there was motivation that made students enthusiastic about learning without cheating behaviour, namely coming from extrinsic motivation in the form of rewards in learning given by teachers and parents. The award is in the form of prizes such as money and credit, accumulated points which can later be used to avoid the next daily test, as well as bonus scores that can be used for additional scores in the race for class rank. On the other hand, there are consequences that cause students' learning motivation, namely buying class tools and memorising if they get low scores. Meanwhile, extrinsic motivation in the form of learning environment conditions is not one of the causes in the spirit of learning.